Microsoft Azure Cosmos DB Developer Specialty (DP-420) Cert Prep: 3 Integrate an Azure Cosmos DB Solution by Microsoft Press. - Warner, Tim; Press, Microsoft (linkedin.com, 2023)
Learn the skills you need to master to tackle the third domain of the Microsoft Azure Cosmos DB Developer Specialty (DP-420) certification exam.